2015
DOI: 10.1253/circj.cj-15-0485
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Problems Late After Arterial Switch Operation for Transposition of the Great Arteries

Abstract: Background:The incidence of late coronary artery abnormalities after arterial switch operation (ASO) for d-loop transposition of the great arteries may be underestimated. Methods and Results:We retrospectively reviewed coronary artery morphology in 40 of 97 patients who survived the first year after ASO. Seven asymptomatic patients developed significant late coronary artery abnormalities. One patient died suddenly at home with severe left coronary artery (LCA) ostial stenosis at age 3.8 years. The second patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 38 publications
1
27
0
5
Order By: Relevance
“…5 We know that the frequency of such features is significant, 5,6,7,19 and our study shows that they cannot be reliably predicted using basic screening tests. A similar conclusion was published by Tsuda et al 20 For responsible patient management, for example, in terms of sports qualification, further follow-up visits and establishing the real impact of the coronary anatomy during the post-operative follow-up are needed to determine the exact coronary pattern in every single patient after an arterial switch operation.…”
Section: Discussionsupporting
confidence: 60%
“…5 We know that the frequency of such features is significant, 5,6,7,19 and our study shows that they cannot be reliably predicted using basic screening tests. A similar conclusion was published by Tsuda et al 20 For responsible patient management, for example, in terms of sports qualification, further follow-up visits and establishing the real impact of the coronary anatomy during the post-operative follow-up are needed to determine the exact coronary pattern in every single patient after an arterial switch operation.…”
Section: Discussionsupporting
confidence: 60%
“…There are currently many exercise studies in children,27 28 mainly focusing on peak oxygen uptake as the outcome parameter, that have shown that exercise is safe and with a minimum of structured training, improvements can be achieved. However, before participation an incidence of coronary stenosis or occlusion has to be ruled out because it is not an infrequent sequel after reimplantation of the coronary arteries in anatomical repair of TGA 29. Particularly dangerous in terms of exercise is that children do not get angina after anatomical repair of TGA as the pain fibres to the heart have been transected which take time to grow back 29…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery obstruction has been reported in 6.8% through 11.3% of patients with transposition of the great arteries (TGA) after arterial switch operation, but these are usually due to mechanical obstruction of the vessels [41,42]. Freedom from coronary events was 88.1 AE 6.4% at 22 years in one study comprising 95 patients [43].…”
Section: Patients At Additional Riskmentioning
confidence: 99%